An unusual cause of Steven-Johnson Syndrome - De Guido, Claudia; Calderaro, Adriana; Ruozi, Maria Beatrice; Maffini, Valentina; Varini, Margherita; Lapetina, Irene; Rubini, Monica; Montecchini, Sara; Caffarelli, Carlo; Dodi, Icilio (Acta Biomedica Atenei Parmensis, 2020)
SJS is a rare mucocutaneous syndrome characterized by skin and mucous detachment. The main etiological factors are drugs and infections; sometimes the cause remains unknown. In the prodromal phase we observed non-specific symptoms, followed by mucocutaneous manifestation. Due to risk of complications and mortality a multidisciplinary approach is needed.  We present a case of a girl with an atypical presentation of SJS related to Enterovirus.